ULTRASONOGRAPHIC IMAGE OF UTERINE INVOLUTION IN POSTPARTUM SAHIWAL COWS - POYAM, M R; TIWARI, R P (The Indian Journal of Animal Reproduction, 2023)
A total of 24 Sahiwal cows with normal parturition were selected and randomly divided into primiparous (n= 12) and pluriparous (n=12 groups) which were further sub divided based on Body Condition Score (BCS) 2-3 (n = 6) and BCS 3-4 (n=6) for monitoring uterine involution during postpartum period. The uterine involution was monitored by measuring diameter of Previous Gravid Uterine Horn (PGUH), Previous Non-Gravid Uterine Horn (NPGUH) and Cervix using Ultrasonographic images from day 14 to 44 postpartum at six days interval. The diameter (mm) of previous gravid uterine horn (PGUH) on day 14, 20, 26, 32, 38 and 44 postpartum was 33.9 ± 2.36, 30.81 ± 2.14, 28.205 ± 2.03, 25.49 ± 1.82, 23.93 ± 1.7 and 21 .91 ± 1.51 respectively. The diameter (mm) of previous non-gravid uterine horn (NPGUH) on day 14,20,26, 32, 38 and 44 postpartum was 6.35 ± 1.19, 5.49 ± 1.17, 5.2 ± 0.97, 4.79 ± 0.94, 4.13 ± 0.96 and 3.72 ± 0.78 respectively There was significant effect of parity on diameter of previous gravid uterine horn (PGUH) and previous non-gravid uterine horn (NPGUH) from day 14 to day 44 postpartum. There was no significant effect of body condition score on uterine involution of both previous gravid uterine horn (PGUH) and previous non-gravid uterine horn (NPGUH). The diameter (mm) of cervix on day 14,20,26, 32, 38 and 44 postpartum was 47.11±2.29, 43.8 ± 2.41, 40.53 ± 1.90, 37.78 ± 1.63, 35.61 ± 1.34 and 33.34 ± 1.17 respectively. There was significant effect of parity on diameter of cervix from day 14 to day 44 postpartum.
Keywords: Body Condition Score; Parity; Primiparous; Pluriparous; Uterine horn